2004
DOI: 10.1073/pnas.0402901101
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory aptamer reveals serum response element transcription regulated by cytohesin-2

Abstract: Cytohesins are a family of highly homologous guanine nucleotide exchange factors (GEFs) that act on ADP-ribosylation factors (ARFs). The small ARF-GEFs are involved in integrin signaling, actin cytoskeleton remodeling, and vesicle transport. Here, we selected and applied a specific inhibitor for ARF nucleotide-binding site opener (ARNO)͞cytohesin-2, an RNA aptamer that clearly discriminates between cytohesin-1 and cytohesin-2. This reagent bound to an N-terminal segment of cytohesin-2 and did not inhibit ARF-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 33 publications
2
40
0
2
Order By: Relevance
“…The aptamer possesses high specificity toward GRK2 as compared to other kinases and thus represents a promising starting point for the functional interference and analysis of endogenous GRK2 function inside cells and living organisms. For example the aptamer can be either directly transfected into cells or expressed from plasmids that encode the aptamer sequence under certain promoter elements (Mayer et al 2001;Theis et al 2004;Famulok and Mayer 2005). Recent studies demonstrated that aptamers can be converted into small molecule inhibitors using so-called aptamer-displacement assays (Hafner et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The aptamer possesses high specificity toward GRK2 as compared to other kinases and thus represents a promising starting point for the functional interference and analysis of endogenous GRK2 function inside cells and living organisms. For example the aptamer can be either directly transfected into cells or expressed from plasmids that encode the aptamer sequence under certain promoter elements (Mayer et al 2001;Theis et al 2004;Famulok and Mayer 2005). Recent studies demonstrated that aptamers can be converted into small molecule inhibitors using so-called aptamer-displacement assays (Hafner et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is at present unknown how the interaction of ARNO/cytohesin-2 with the A 2A receptor supports sustained activation of MAP kinase. However, it is not without precedent; inhibition of ARNO/cytohesin-2 was recently found to down-regulate mitogen-activated protein kinase activation in HeLa cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an in vitro selected RNA aptamer was used to discriminate the roles of two highly homologous protein, cytohesin 1 and cytohesin 2, in regulating gene expression in response to serum stimulation (30). This aptamer binds to the N-terminal segment of cytohesin-2 specifically and can down-regulate expression of genes mediated though its serum response element and reduce mitogen-activated protein kinase activation in HeLa cells, suggesting a specific role of cytohesin-2 but not cytohesin-1 in serum-mediated transcriptional activation in nonimmune cells.…”
Section: Discussionmentioning
confidence: 99%